International prevalence of tactile map usage and its impact on navigational independence and well-being of people with visual impairments - Maxime Bleau; Kopila Kafle; Min Wang; Soutongnoma Safiata Kabore; Jorge Luis Cueva-Vargas; Joseph Paul Nemargut (Scientific Reports)
Abstract For people with visual impairments (PVI), understanding space is crucial for independence and tactile maps are useful tools to gain spatial information and improve orientation. However, their popularity and impacts in the PVI population are not yet fully understood. Thus, this study aims to determine the prevalence of tactile map usage and their effects on independent travel and well-being internationally. To do so, two online surveys were completed by PVI (n1 = 752, n2 = 510) in 40 countries from which information was collected related to travel habits, spatial abilities, experience with tactile maps, mobility services, and perceived well-being. The surveys revealed that only 17.15% of respondents have had experience with tactile maps and that this tactile map experience was related to better cognitive mapping skills, a higher level of education, a higher perceived well-being and a higher sense of independence (i.e., perceiving the area of living as more accessible, and requiring assistance less often). This study confirms that tactile maps have a positive impact on the independent travel and well-being of PVI around the world, including both individuals with low-vision and blindness, and demonstrates the importance of early tactile map exposure, as tactile maps support the development of generalizable spatial concepts and abilities.